Within the lighted city - Lenzo, Lisa, 1957- (John Simmons short fiction award., 1997)
A collection of interwoven stories set in Detroit. The story, Burning, is on the 1967 race riot, in Self-Defense, a white girl is attacked by black students, and Sophie's Shirt is a mother's grief at the loss of a baby.